Benefits of the application of the GRI in organizations (Journal of Management & Business, 2025)
This paper analyzes a set of articles, in order to obtain the benefits of the integration of GRI reports in organizations, for this purpose, 672 articles from the SCOPUS database have been used. This was done through a theoretical review, guided by the systematic review methodology based on PRISMA strategies. From this, it was excluded according to established criteria, where this process obtained 33 articles related to the purpose of which 6 results could be obtained according to analysis. On the other hand, we concluded benefits originated for the organizations due to the use of these indicators, which were in environment (1), production (2), marketing (3), financial(4), decision making (5), and finally, in the management of human talent(6). In summary, the integration of the GRI reports has determined benefits for the organizations that integrate it, therefore, its use must be in an adequate manner so that the results obtained are achieved.
Keywords: financial benefit; environmental benefit; talent management benefit; marketing benefit; decision making benefit; production benefit; sustainability; industry; responsibility